Elastofibroma: Literature Review and Clinical Case Report (Global Journal of Medical Research, 2023)
Elastofibroma is a rare slowly growing benign soft tissue tumor of mesenchymal origin characterized by typical localization in the subscapular region It consists of proliferating fibrous and adipose tissue The first elastofibroma was diagnosed in 1958 1 The first clinical case called Elastofibroma of the Back was presented at the XII Scandinavian Congress of Pathologists by doctors O Jarvi and A E Saxen However this case was published only in 1961 2 3